﻿Diversity underfoot of agromyzids (Agromyzidae, Diptera) mining thalli of liverworts and hornworts - Makoto Kato; Luna Yamamori; Yume Imada (ZooKeys, 2022)
Agromyzidae is a dipteran family that has diversified as internal plant feeders. Although most agromyzid species feed on herbaceous angiosperms, only a limited number of species has been recorded as miners of bryophytes. Extensive searches and rearing of bryophytivores in the Japanese Archipelago were made, resulting in that thallus-mining agromyzids are overwhelmingly widespread and diverse on thalloid liverworts and hornworts. By examining the morphology of adult flies, it was revealed that the agromyzid fauna comprise 39 species, of which 37 species are newly described. All the species are assigned to the genus Phytoliriomyza Hendel based on some shared morphological character states as follows: costa reaching M1; orbital setulae minute and erect (rarely proclinate); male epandrium with combs of fused tubercle-like setae and/or hypertrophied arms bearing tubercle-like setae; male distiphallus comprising a pair of stout, extended tubules; female cercus with two stout, apical, trichoid sensilla. Of the 39 agromyzid species in Japan, 36 species are associated with liverworts: 5 spp. on Marchantia (Marchantiaceae), 2 spp. on Dumortiera (Dumortieraceae), 3 spp. on Plagiochasma, 1 sp. on Asterella, 6 spp. on Reboulia (Aytoniaceae), 1 sp. on Wiesnerella (Wiesnerellaceae), 15 spp. on Conocephalum (Conocephalaceae), and 3 spp. on Riccia (Ricciaceae). Three species are associated with hornworts: 1 sp. on Folioceros (Anthocerotaceae), 1 sp. on Megaceros (Dendrocerotaceae), and 1 sp. on Notothylas, Phaeoceros (Notothyladaceae), and Anthoceros (Anthocerotaceae). The results suggest that 37 of the 39 species are host-specific at least to plant genus level, and that the inter-specific differences in male genitalia and color patterns of scutum, antenna, and maxillary palpus have contributed to reproductive isolation on the bryophytes that the flies share.